Composites Based on Polylactide Doped with Amorphous Europium(III) Complex as Perspective Thermosensitive Luminescent Materials - Andrey A. Knyazev; Aleksandr S. Krupin; Yuriy G. Galyametdinov (Inorganics, 2022)
This work reports fabrication of polylactide (PLA) films doped with various additives of an amorphous Eu(III) complex. We study the temperature behavior of the luminescence intensity and lifetime of the PLA-Eu(III) composites in the range of 298–353 K and investigate the mechanism of luminescence temperature quenching. The peak relative sensitivity of the films reaches 20.1 %×K−1 and exceeds the respective characteristics of all known lanthanide-containing thermosensors designed for the range of physiological temperatures. The produced films can be potential novel materials for luminescent thermosensors.